2009
DOI: 10.1007/s00213-009-1599-z
|View full text |Cite
|
Sign up to set email alerts
|

The d-amphetamine-treated Göttingen miniature pig: an animal model for assessing behavioral effects of antipsychotics

Abstract: Rationale Rodents are usually used to assess the ability of antipsychotic drugs to antagonize hyperlocomotion induced by dopamine agonists, such as the psychostimulant d-amphetamine. However, the substantial differences between rodents and humans may hinder extrapolation of experimental results to humans. For this reason, we speculated that Göttingen miniature pigs, which show strong physiological and genetic homology with humans, might be a better model for investigating the effects of antipsychotics. To inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…A recent increase in the use of pigs as models in neuroscience, cognition, and neurobehavioral studies is due to the close similarity in brain development, growth and anatomy to humans ( Dickerson and Dobbing, 1966 ; Gieling et al, 2011 ; Glauser, 1966 ; Lind et al, 2007 ; Lunney, 2007 ; Thibault and Margulies, 1998 ). Porcine models for translational research of schizophrenia ( Lind et al, 2005 ; Lind et al, 2004 ), antipsychotic interventions ( van der Staay et al, 2009 ), epilepsy ( Marchi et al, 2007 ), intrauterine growth restriction ( Bauer et al, 2007 , Burke et al, 2006 , Ferenc et al, 2014 , Gonzalez-Bulnes et al, 2016 ), learning ( Andersen et al, 2016 ), and social interactions ( Kanitz et al, 2016 ) have been also developed. Pigs are multiparous animals with the same or larger litters than in mice and the length of gestation in pigs, 114 days, closely approximates gestation in humans.…”
Section: Introductionmentioning
confidence: 99%
“…A recent increase in the use of pigs as models in neuroscience, cognition, and neurobehavioral studies is due to the close similarity in brain development, growth and anatomy to humans ( Dickerson and Dobbing, 1966 ; Gieling et al, 2011 ; Glauser, 1966 ; Lind et al, 2007 ; Lunney, 2007 ; Thibault and Margulies, 1998 ). Porcine models for translational research of schizophrenia ( Lind et al, 2005 ; Lind et al, 2004 ), antipsychotic interventions ( van der Staay et al, 2009 ), epilepsy ( Marchi et al, 2007 ), intrauterine growth restriction ( Bauer et al, 2007 , Burke et al, 2006 , Ferenc et al, 2014 , Gonzalez-Bulnes et al, 2016 ), learning ( Andersen et al, 2016 ), and social interactions ( Kanitz et al, 2016 ) have been also developed. Pigs are multiparous animals with the same or larger litters than in mice and the length of gestation in pigs, 114 days, closely approximates gestation in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the pig is responsive to amphetamine. Pigs have been used to demonstrate amphetamine-induced hyperlocomotion (van der Staay et al 2009) and DA release in response to amphetamine (Lind et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Compared with esophageal squamous mucosa, hypopharynx mucosa is easily injured by reflux contents. 29 In the esophagus, upper limit of tolerance to GER is 50 times per day in the normal physiological condition, but in the hypopharynx, upper limit is generally below 7 times per day.…”
Section: Discussionmentioning
confidence: 99%